Inhibition of Agonist-Induced Positive Inotropy by a Selective Rho-Associated Kinase Inhibitor, Y-27632 - Kazuhide Nishimaru; Yoshio Tanaka; Hikaru Tanaka; Koki Shigenobu (Elsevier, 2003)
We examined the effect of Y-27632 ((+)-(R)-trans-4-(1-aminoethyl)-N-(4-pyridyl)cyclo-hexanecarboxamide), a selective Rho-associated kinase (ROCK) inhibitor, on agonist-induced inotropy in isolated mouse left atria. Endothelin-1, angiotensin-II, and prostaglandin F2α (PGF2α) produced positive inotropy, which was significantly attenuated by Y-27632 (100 μM). On the other hand, isoproterenol-induced positive inotropy was not attenuated by the drug. These results provide the first evidence that the Rho/ROCK pathway is involved in endothelin-1-, angiotensin-II-, and PGF2α-induced positive inotropy, but not in β-adrenoceptor-mediated positive inotropy.